The New Muslims of Post-Conquest Iran : Tradition, Memory, and Conversion. - Savant, Sarah Bowen (Cambridge studies in Islamic civilization., 2013)
This book focuses on the role of memory and its revision and erasure in the ninth to eleventh centuries.